A case study of group art therapy using digital media for adolescents with intellectual disabilities - Kim, Jinkyung; Chung, Yeo Ju (Frontiers in Psychiatry, 2023)
Introduction In art therapy, digital art therapy is a new method in which clients use digital media to express themselves creatively. We wanted to explore what this means for adolescents with disabilities. The purpose of this qualitative case study was to explain what kind of experience they had when digital media was applied as an expressive and therapeutic medium in group art therapy in which adolescents with intellectual disabilities were participants and what kind of therapeutic meaning the experience had. We tried to know the therapeutic factors by extracting the implications of meaning. Methods Participants were second-year high school students with intellectual disabilities who belonged to special classes. They were selected in an intentional purposive sampling method. Five teenagers with intellectual disabilities participated in 11 group art therapy sessions. Data were collected through interviews, observation, and digital artwork collection. Collected data were case studies analyzed using an inductive approach. In this study, the use of digital media was defined and utilized as “Digital Art Therapy” by setting the scope related to the study according to client’s behavioral method. Results As a digital generation accustomed to smartphones, the participants gained confidence by repeatedly acquiring new technologies through familiarity with the media. Interaction with the media through touch and the use of apps have promoted autonomy with interest and pleasure to disabled teenagers, allowing them to express themselves actively. In particular, digital art therapy induces a holistic sensory experience by mobilizing visual images that could represent various expressions, emotions felt in music and tactile senses that made texts for people with intellectual disabilities with difficulty in verbal communication. Discussion Art therapy using digital media has become an important experience that provides opportunities to arouse curiosity, enjoy creative activities, and express positive emotions vividly to adolescents with intellectual disabilities who have difficulties with expression and communication and a sense of lethargy. Therefore, it is suggested that an in-depth understanding of the characteristics and differences between traditional and digital media is necessary, and that complementary use to help create therapeutic purposes and art therapy is important.